2003
DOI: 10.1095/biolreprod.103.015610
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Molecular Aberrations Associated with Deterioration of Oogenesis During Complete or Partial Follicle-Stimulating Hormone Receptor Deficiency in Mice

Abstract: Targeted disruption of the mouse FSH receptor gene (FSH-R) that mediates the action of the FSH results in a gene dose-related ovarian phenotype in the developing as well as the adult animal. While null females (FORKO) are sterile, the haplo-insufficient mice experience early reproductive senescence. The purpose of this study was to first record changes in oocyte development in the null FORKO and haplo-insufficient mice. Oocyte growth is significantly retarded in the null mutants with thinner zona pellucida in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 42 publications
3
33
0
1
Order By: Relevance
“…These phenotypic changes were accompanied by circulating reproductive hormonal imbalance. Further molecular analysis of ovarian marker genes including those involved in oocyte and granulosa cell growth and development confirmed that the oocyte-somatic cell interactions were perturbed (Balla et al 2003, Yang et al 2003b. During this accelerated aging in heterozygous mice, prominent uterine pathology was also evident.…”
Section: Female Reproductive Phenotypes In Forko Micementioning
confidence: 80%
See 1 more Smart Citation
“…These phenotypic changes were accompanied by circulating reproductive hormonal imbalance. Further molecular analysis of ovarian marker genes including those involved in oocyte and granulosa cell growth and development confirmed that the oocyte-somatic cell interactions were perturbed (Balla et al 2003, Yang et al 2003b. During this accelerated aging in heterozygous mice, prominent uterine pathology was also evident.…”
Section: Female Reproductive Phenotypes In Forko Micementioning
confidence: 80%
“…The heterozygous mice initially had reduced fertility and they stopped breeding by 7 -9 months. There was an accelerated loss of oocytes as a result of atresia and apoptosis that are typical characteristics of reproductive senescence (Balla et al 2003, Yang et al 2003b. These phenotypic changes were accompanied by circulating reproductive hormonal imbalance.…”
Section: Female Reproductive Phenotypes In Forko Micementioning
confidence: 99%
“…Whereas FSH stimulates GDF9 production by hamster postnatal ovaries in vitro [18], the BMP15 protein is downregulated in both Fshr-null and Fshr þ/À ovaries, indicating that FSHR and BMP15 have a direct relationship, at least at the level of translation of the latter [19]. However, a recent in vitro study in the mouse [20] has shown that, depending on the dose, FSH had either no significant effect or significantly decreased Bmp15 expression by oocyte-granulosa cell complexes from preantral follicles when compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrastructural study also showed apoptotic changes in the OP-treated and atretic groups; the pattern of apoptosis differed at the subcellular level. (J Histochem Cytochem 56:961-968, 2008) K E Y W O R D S octapeptide apoptotic markers immunohistochemistry flow cytometry electron microscopy intraovarian factors follicle-stimulating hormone binding inhibitor OVARIAN FOLLICULAR DEVELOPMENT is a continuous process wherein the resting follicles develop to form a mature Graffian follicle under the influence of pituitary gonadotropins follicle-stimulating hormone (FSH) and luteinizing hormone (LH) (Yang et al 2003). It is well documented that, in addition to gonadotropins, intraovarian factors are also involved in the regulation of folliculogenesis (Armstrong and Webb 1997).…”
mentioning
confidence: 99%